An Artifact for Evaluating the Quality of Health Service Providers: Evidence From Brazil - Lúcia Helena da Silva Mendes MSc; Luiz Cláudio Sampaio Mendes MSc; Lilian Lucy dos Santos MSc; Carlos Otávio Senff PhD; Claudimar Pereira da Veiga PhD; Luiz Carlos Duclós PhD (SAGE Publishing, 2018)
The aim of this article is to present an artifact for evaluating the quality and performance of service providers in the field of health care: the UNIPLUS Program. To verify the scientific nature of the artifact and ensure that it meets the criteria set by the community and the environment, the premises of Design Science Research (DSR) were used. As this research field lacks empirical evidence, the artifact was tested from 2013 to 2015 with 25 health care service providers from different categories, with an emphasis on hospitals and clinics located in 7 cities in the south of Brazil. This article makes 3 main contributions to the field: (1) the artifact can be applied to any health insurance operator in Brazil and other countries, as it meets the legal norms and requirements established by current legislation; (2) it helps health service providers by generating information that identifies shortfalls and possibilities for improvement for every aspect analyzed in the evaluation process; and (3) it uses the DSR methodology in an evaluation artifact that evaluates the quality and performance of services in the field of health care. The artifact proved to be adequate for the purpose in question, helping to improve the quality of care and institutional performance.